Hegel’s Naturalism? (Revista Eletrônica Estudos Hegelianos, 2016)
ABSTRACT: The recent tendency to detect naturalism in Hegel’s epistemology is more than just a phenomenon within contemporary Anglophone scholarship, insofar as it mirrors a questionable state of the art at the intersection between philosophy of science and philosophy of mind. According to the naturalist reading, Hegel maintains that the natural world is the only presupposition for satisfying the needs of self-consciousness. Such reading considers the essence of self-consciousness as naturally embodied in its essence, while downplaying the intersubjective dimension of reciprocal recognition needed for self-consciousness. Self-consciousness, as the thinking subject or the mind, is then lead to allegedly unavoidable delimitation of any knowledge-claims. On this reading, the natural is an insurmountable obstacle to the mind. Hegel, on his side, evidently offers an ongoing multifaceted dialogue with divergent streams of naturalism. Yet, the question arises: in which sense can we appropriately speak of Hegel’s naturalism? This paper presents the recent naturalistic approaches to Hegel, along with deliberations on Hegel’s possible response to them, namely his concept of the transsubjective thinking mind, the Geist.